Restoring Good Hope: rock art in the age of digital reproduction - Guy, J.; Wintjes, J. (Southern African Humanities, 2021)
This article is a contribution to the long controversy about the restoration of works of art - in this case rock painting. We apply digital imaging techniques to the century-old historical pictorial record of the paintings at Good Hope Shelter, a badly vandalized and deteriorated rock art site in the Sani Pass area of the southern Drakensberg in KwaZulu-Natal. We demonstrate ways in which the pixel image is qualitatively different from pre-digital techniques of recording and replication. We propose a technique of digital restoration that roots itself firmly in the work of previous researchers and bypasses many of the problems that the physical restoration of a site like this would pose. We also argue that in the digital era the idea of an ’original’ rock art image can be dynamically re-imag(in)ed and contextualized. Instead of removing the image into the static printed-paper world, digital imaging can bring us closer to the materiality and physical presence of rock art and its essentially dynamic and unfinished visual qualities. To cite this article: Guy, J. & Wintjes, J. 2009. Restoring Good Hope: rock art in the age of digital reproduction. Southern African Humanities 21: 63-84.